Pengembangan Media Pembelajaran Berbasis E-Comic pada Materi Sistem Respirasi untuk Meningkatkan Motivasi Belajar Siswa SMA - Amalia, Dian Rizki Kusuma; Indrowati, Meti; Oetomo, Dwi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2022)
This research aims to (1) Knowing the development of e-comic-based learning media (ResDiC) on respiratory system material to increase high school students' learning motivation, (2) Knowing the feasibility of e-comic-based learning media (ResDiC) on respiratory system material to increase high school students' learning motivation, (3) Knowing response of student and teacher to e-comic-based learning media (ResDiC) on the respiratory system material to increase high school students' learning motivation, (4) Knowing the results of implementing e-comic-based learning media (ResDiC) on high school students' learning motivation. This research is kind of research and development (RnD). The development model used is ADDIE (analyse, design, development, implementation, evaluation). This research was conducted at MAN Sukoharjo. The research subjects were validators of media experts, material experts, teachers, and students. Data collection techniques in the form of teacher interviews, and need analysis questionnaires, material validation, media validation, teacher responses, student responses, and student learning motivation. The analysis used is Rasch analysis. ResDiC e-comic media is a learning media that contains material on the respiratory system which is presented in the form of interesting comics with various images and is equipped with videos related to the material. ResDiC is an e-comic that can be accessed with smartphones and laptops. The results of expert validation stated that the ResDiC media was very feasible to be used in research and learning. The response of teachers and students to the ResDiC media is also good. ResDiC media with its attractive appearance has the potential to increase students' learning motivation. The results of the pre and post motivational questionnaire showed an increase of 3.4%% for high motivation classes and an increase of 10% for moderate motivation classes after using ResDiC media.